Three-dimensional nanotubes composed of carbon-anchored ultrathin MoS2 nanosheets with enhanced lithium storage. Issue 29 (8th July 2016) - Yi, Fenglian; Niu, Yubin; Liu, Sangui; Hou, Junke; Bao, Shujuan; Xu, Maowen
Abstract : MoS2 nanotubes (denoted as MoS2 NTs) assembled from well-aligned amorphous carbon-modified ultrathin MoS2 nanosheets (denoted as MoS2 NT@C) were successfully fabricated via a facile solvothermal method combined with subsequent annealing treatment. Abstract : MoS2 nanotubes (denoted as MoS2 NTs) assembled from well-aligned amorphous carbon-modified ultrathin MoS2 nanosheets (denoted as MoS2 NT@C) were successfully fabricated via a facile solvothermal method combined with subsequent annealing treatment. With the assistance of octylamine as a solvent and carbon source, interconnected MoS2 nanosheets (denoted as MoS2 NSs) can assemble into hierarchical MoS2 NTs. Such a hybrid nanostructure can effectively facilitate charge transport and accommodate volume variation upon prolonged charge/discharge cycling for reversible lithium storage. As a result, the MoS2 NT@C composite manifests a very stable high reversible capacity of around 1351 mA h g −1 at a current density of 100 mA g −1 ; even after 150 cycles, the electrode reaches a capacity of 1106 mA h g −1 and it retains a reversible capacity of 650 mA h g −1 after the 10th cycle at a current density of 3 A g −1, all of which indicate that the MoS2 NT@C nanocomposite is a promising negative electrode material for high-energy lithium ion batteries.